1994
DOI: 10.1002/bjs.1800810626
|View full text |Cite
|
Sign up to set email alerts
|

Conservative initial treatment for liver abscesses in children

Abstract: A total of 124 children aged less than 14 years with a liver abscess were seen in a 16-year period (1974-1990) and treated by non-operative initial management. Of the abscesses 98 occurred in the right liver and 26 in the left. The abscesses were solitary in 93 patients. Overall, 77 of the solitary and 21 of the multiple abscesses were confined to the right liver. In 78 of the right-sided and 20 of the left-sided abscesses the infection was primarily pyogenic in nature with Staphylococcus aureus being the usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…[21] Causative organism Pyogenic organisms account for nearly 80% of LA in children, followed by amebic LA which is responsible for about 21%-30% of the cases. [1][2][3] Worldwide, the most common pathogen isolated from LA in children is Staphylococcus aureus both in developed and developing countries. [4,22] Studies from India revealed similar results.…”
Section: Review Articlementioning
confidence: 99%
See 4 more Smart Citations
“…[21] Causative organism Pyogenic organisms account for nearly 80% of LA in children, followed by amebic LA which is responsible for about 21%-30% of the cases. [1][2][3] Worldwide, the most common pathogen isolated from LA in children is Staphylococcus aureus both in developed and developing countries. [4,22] Studies from India revealed similar results.…”
Section: Review Articlementioning
confidence: 99%
“…[1][2][3] Studies from the United States suggest that 1%-7% of the population is infected with Entamoeba histolytica and less than 1% of the infected have extraintestinal disease. [28] Fungal hepatic microabscesses either alone or in association with splenic microabscesses may occur in children with leukemia.…”
Section: Review Articlementioning
confidence: 99%
See 3 more Smart Citations